Reading and visual word recognition ability in semantic dementia is not predicted by semantic performance. (March 2018) - Playfoot, David; Billington, Jac; Tree, Jeremy J.
Abstract: This paper describes longitudinal testing of two Semantic Dementia (SD) cases. It is common for patients with SD to present with deficits in reading aloud irregular words (i.e. surface dyslexia), and in lexical decision. Theorists from the connectionist tradition (e.g. Woollams et al., 2007) argue that in SD cases with concurrent surface dyslexia, the deterioration of irregular word reading and recognition performance is related to the extent of the deterioration of the semantic system. The Dual Route Cascaded model (DRC;Coltheart et al., 2001 ) makes no such prediction. We examined this issue using a battery of cognitive tests and two structural scans undertaken at different points in each cases time course. Across both cases, our behavioural testing found little evidence of a key putative link between semantic impairment and the decline of irregular word reading or lexical decision. In addition, our neuroimaging analyses suggested that it may be the emergence of atrophy to key neural regions both inside and outside the anterior temporal lobes that may best capture the emergence of impairments of irregular word reading, and implicated inferior temporal cortex in surface dyslexia. Highlights: Reading aloud of irregular words is not predicted by semantic performance in SD. Lexical decision accuracy is not predicted by semantic performance in SD. Surface dyslexia is not solely related to anterior temporal lobe damage. Inferior temporal cortex is implicated in irregular word reading deficits.